2019
DOI: 10.2134/agronj2018.03.0223
|View full text |Cite
|
Sign up to set email alerts
|

Plant Population and Fungicide Economically Reduced Winter Wheat Yield Gap in Kansas

Abstract: Despite the large differences between winter wheat (Triticum aestivum L.) current and potential yields (i.e., yield gap, YG) in Kansas, limited research is available on individual agronomic practices, or their combination, economically increasing yield. Our objective was to quantify the contribution of individual and combined management practices to reduce the wheat YG. An incomplete factorial treatment structure established in a randomized complete block design was conducted to evaluate the effects of 14 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
64
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 59 publications
18
64
0
2
Order By: Relevance
“…These results agree with published studies indicating that foliar fungicides are among the most important variables in intensively managed wheat systems ( Jaenisch et al, 2018). These results agree with published studies indicating that foliar fungicides are among the most important variables in intensively managed wheat systems ( Jaenisch et al, 2018).…”
Section: Potential Management Practices To Reduce Wheat Yield Gaps Insupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with published studies indicating that foliar fungicides are among the most important variables in intensively managed wheat systems ( Jaenisch et al, 2018). These results agree with published studies indicating that foliar fungicides are among the most important variables in intensively managed wheat systems ( Jaenisch et al, 2018).…”
Section: Potential Management Practices To Reduce Wheat Yield Gaps Insupporting
confidence: 93%
“…Still, it is characterized by wheat grain yields that are stagnant (Patrignani et al, 2014) and low (?2.5 to 3.0 Mg ha −1 ; Licker et al, 2010). However, with few exceptions (e.g., Jaenisch et al, 2018), most of the manageable agronomic practices in this region were explored in low-and average-yielding systems, ranging between 2 and 4 Mg ha −1 (Edwards et al, 2011;Schroder et al, 2011;Bushong et al, 2012;Lollato et al, 2013). However, with few exceptions (e.g., Jaenisch et al, 2018), most of the manageable agronomic practices in this region were explored in low-and average-yielding systems, ranging between 2 and 4 Mg ha −1 (Edwards et al, 2011;Schroder et al, 2011;Bushong et al, 2012;Lollato et al, 2013).…”
Section: Agronomic Practices For Reducing Wheat Yield Gaps: a Quantitmentioning
confidence: 98%
“…Kelley (1993) found that fungicide use resulted in higher test weight in five of seven site-years across multiple cultivars. Photosynthates are necessary to fill wheat kernels and increase test weight, and leaf area protection under the high-disease scenarios with fungicide use likely explains our results (Jaenisch et al, 2019).…”
Section: Crop Sciencementioning
confidence: 68%
“…Jaenisch et al. () did not evaluate single fungicide applications, but the authors found that fungicide applied at Feekes 6 and Feekes 10.5 to winter wheat in Kansas was economical in high‐disease site‐years and when a low‐cost fungicide product and protein premium were considered. Additionally, one and two fungicide application partial profit results in this study were similar to the nontreated control or significantly negative when disease levels were low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation